Qualitative and quantitative estimation of Diosgenin in coded ayurvedic formulation and its ingredient Trigonella foenum-graecum Linn. seeds used in diabetics - Ajay Kumar Meena; K. N. Swathi; R. Ilavarasan; Arjun Singh; Vandana Bharthi; N. Srikanth (SpringerOpen, 2021)
Abstract Background Trigonella foenum-graecum (Methi) is a leguminous plant and botanically known as Trigonella foenum-graecum Linn, belong to the family Fabaceae. Trigonella foenum-graecum is used for a variety of health conditions, including digestive problems, bronchitis, tuberculosis, fevers, sore throats, wounds, arthritis, abscesses, swollen glands, skin irritations, diabetes, loss of appetite, ulcers, and menopausal symptoms, as well as in the treatment of cancer. Trigonella foenum-graecum seeds mainly contain Diosgenin [(3β,25R)-spirost-5-en3-ol], a plant-derived steroid sapogenin. Results The identification and quantification results by HPTLC and HPLC studies of Trigonella foenum-graecum seeds hydrolysed Trigonella foenum-graecum seeds, coded formulation, hydrolysed coded formulation extract with standard Diosgenin biomarker showed a significant highest peak in hydrolysed Trigonella foenum-graecum seeds and hydrolysed coded formulation. The standard Diosgenin is observed in the hydrolysed form of hydrolysed Trigonella foenum-graecum seeds and hydrolysed coded formulation. The literature on Trigonella foenum-graecum confirms its activity as antidiabetic, and the peak of standard biomarker Diosgenin is seen after derivatization with anisaldehyde sulphuric agent, which possesses medicinal phytoconstituents value. Further related to future scientific aspects, more studies on its potent antidiabetic activity and multipurpose action need to be carried out with medicinal composition and its effects on the human body. Conclusion This study aims to establish the qualitative and quantitative estimation of standard Diosgenin in reliable with coded ayurvedic formulation and Trigonella foenum-graecum seeds and its activity as antidiabetic by HPTLC and HPLC.